Evaluation of praecordial ST segment mapping as an index of infarct size in patients with acute myocardial infarction. Issue 6 (December 1979) - Inoue, M; Hori, M; Fukunami, M; Fukushima, M; Tada, M; Abe, H; Minamino, T; Fukui, S
Abstract : We evaluated the usefulness and limitations of praecordial ST segment mapping as a clinical means of assessing the size of acute myocardial infarction in 14 patients with anterior myocardial infarction and 13 patients with inferior myocardial infarction. sigma ST, the sum of ST segment elevations, and nST, the number of leads showing ST segment elevation, were obtained from serial electrocardiograms recorded through 39 praecordial leads. The infarct size and period of the evolution of myocardial infarction were estimated respectively from the total creatine kinase (CK) released and the serial changes of the CK releasing rate. sigma ST and nST obtained at the time when the CK release had ceased correlated closely with the total CK released. Peak sigma ST and nST, and values 48 hours after the onset of myocardial infarction, also correlated well with the total CK released; but those on admission or 12 hours after the onset correlated poorly. These results suggest that sigma ST and nST at the end of evolution of myocardial infarction or 48 hours after the onset may be two useful indices for the assessment of infarct size in patients with either anterior or inferior myocardial infarction.